Tunable Nanosensor With a Horizontal Number Eight-Shape Cavity in a MIM Waveguide System - Xu, Daijing; Yan, Shubin; Yang, Xiaoyu; Wang, Jinxi; Wu, Xiushan; Hua, Ertian (Frontiers in Physics, 2021)
The optical devices play an important role in different fields, such as refractive index detection in food processing and biochemical industry. In our work, a novel nanoscale optical structure, composed metal-insulator-metal (MIM) waveguide with a stub and a horizontal number eight-shape cavity (HNEC), is presented. The transmission properties of this structure are investigated detailedly by using finite element method (FEM). The effects of geometric parameters on sensing performance are studied detailedly. Moreover, the influences of asymmetric resonator caused by shifting central rectangular cavity of HNEC on transmission spectrum are discussed. The changing HNEC resonator have different effects on different resonance dips. Further more, the application of this intriguing structure served as refractive index sensor is studied, whose maximum sensitivity can reach to 1500 nm/RIU with FOM of 75. Therefore, this structure will contribute to the development of miniaturization of the optical device.